Income inequality and product variety: Empirical evidence - Dieter Pennerstorfer; Nora Schindler; Christoph R. Weiss; Biliana Yontcheva (Johannes Kepler University of Linz, Department of Economics, 2020)
This article investigates the relationship between income inequality and firms' locations and product choices. Using detailed information on income at a regionally disaggregated level and individual data on Austrian restaurants, we demonstrate that firm conduct crucially depends on the distribution (in addition to the level) of income. Local markets with higher income inequality are characterized by a larger number of firms, offering a broader range of products and product variants that are on average less common. These findings indicate that local demand is substantially in uenced by the heterogeneity in consumers' income endowments, resulting in large differences in product variety.
Keywords: L22; D31; R12; L83; 330; income inequality; product variety; product differentiation; firm conduct; restaurants